2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2016
DOI: 10.1109/icassp.2016.7472660
|View full text |Cite
|
Sign up to set email alerts
|

Testing the consistency assumption: Pronunciation variant forced alignment in read and spontaneous speech synthesis

Abstract: Forced alignment for speech synthesis traditionally aligns a phoneme sequence predetermined by the front-end text processing system. This sequence is not altered during alignment, i.e., it is forced, despite possibly being faulty. The consistency assumption is the assumption that these mistakes do not degrade models, as long as the mistakes are consistent across training and synthesis. We present evidence that in the alignment of both standard read prompts and spontaneous speech this phoneme sequence is often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Rule-based pronunciation lattices have also been used to reduce inconsistencies between the phoneme sequence generated by the front-end text processing system (i.e. the phonetizer) and the phoneme sequence as transcribed in the training speech corpus [27]. However, building and maintaining such hand-crafted pronunciation lexicons designed by linguistic experts and transpose them to diverse speaking styles and expressivity is expensive and time consuming.…”
Section: Studies On Pronunciation Variants Modellingmentioning
confidence: 99%
“…Rule-based pronunciation lattices have also been used to reduce inconsistencies between the phoneme sequence generated by the front-end text processing system (i.e. the phonetizer) and the phoneme sequence as transcribed in the training speech corpus [27]. However, building and maintaining such hand-crafted pronunciation lexicons designed by linguistic experts and transpose them to diverse speaking styles and expressivity is expensive and time consuming.…”
Section: Studies On Pronunciation Variants Modellingmentioning
confidence: 99%
“…The same result persisted even after a pronunciation variant forced alignment method was applied to compensate for the additional reductions and deletions present in the spontaneous speech. However, the test sentences used in [19] did not contain FPs, and other researchers have found that including these in voices based on spontaneous speech can improve their perceived naturalness to be on par with, or even better than, voices trained on read speech [20,16]. A test was thus performed to confirm whether this is also the case for the corpora used for the experiments reported in this paper.…”
Section: Read and Spontaneous Speech Based Voicesmentioning
confidence: 99%
“…The read and spontaneous speech corpora used in these experiments were the same as those described in [19]. The read corpus consisted of studio recordings of a female British English speaker (recorded at 96khz, 32 bit, downsampled to 48khz, 16 bit), the prompts used were the Arctic sentences [18] and the R. Dall, M. Tomalin, M. Wester corpus contained a total of 1125 sentences (66 mins: 20 mins silence, 46 mins speech).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations